Integration of Modern Information Technologies in the Field of Financial Accounting - Adrian LUPASC; Ioana LUPASC; Cristina Gabriela ZAMFIR (Risk in Contemporary Economy, 2011)
Financial accounting activities are currently influenced as many other important areas that characterize and surrounds the activities within each economic entity, the avalanche of modern information technologies, which are able to improve specific business processes and to ensure future business success. Approach analysis of the impact of new technologies on this field should be so as a starting point to identify the opportunities and the benefits they would bring to specific activities. Information and communication technologies are in use both at the individual level and at the organizational level with the flexibility of the increasingly high, using a huge volume of information that financial accounting with direct impact on all human activities. Basically, it has already made the passage to a new stage:the global network society, whose main features are digitizing and interconnectivity. In this sense, this paper has as its main objective of examining the impact of modern information technologies may have on the financial accounting domain and the identification and submission directions for their integration within organizations.